INFLUENCE OF RISK AND DEMOGRAPHICS ON ONLINE TRADING IN HARYANA STATE: REVIEW OF LITERATURE - Vikram; Kumar, Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper highlights the influence of risk and demographics on online trading and review of literature. In this study, importance of review of literature has been explored. The authors portray that how review of literature gives direction to any study.